Impact of Hepatoma-Derived Growth Factor Blockade on Resiniferatoxin-Induced Neuropathy. (28th February 2021) - Wu, Chieh-Hsin; Wu, Ming-Kung; Lu, Chun-Ching; Tsai, Hung-Pei; Lu, Ying-Yi; Lin, Chih-Lung
Abstract : Resiniferatoxin is an ultrapotent capsaicin analog that mediates nociceptive processing; treatment with resiniferatoxin can cause an inflammatory response and, ultimately, neuropathic pain. Hepatoma-derived growth factor, a growth factor related to normal development, is associated with neurotransmitters surrounding neurons and glial cells. Therefore, the study aims to investigate how blocking hepatoma-derived growth factor affects the inflammatory response in neuropathic pain. Serum hepatoma-derived growth factor protein expression was measured via ELISA. Resiniferatoxin was administrated intraperitoneally to induce neuropathic pain in 36 male Sprague-Dawley rats which were divided into three groups (resiniferatoxin+recombinant hepatoma-derived growth factor antibody group, resiniferatoxin group, and control group) (n = 12 /group). The mechanical threshold response was tested with calibration forceps. Cell apoptosis was measured by TUNEL assay. Immunofluorescence staining was performed to detect apoptosis of neuron cells and proliferation of astrocytes in the spinal cord dorsal horn. RT-PCR technique and western blot were used to measure detect inflammatory factors and protein expressions. Serum hepatoma-derived growth factor protein expression was higher in the patients with sciatica compared to controls. In resiniferatoxin-group rats, protein expression of hepatoma-derived growth factor was higher than controls. Blocking hepatoma-derived growth factor improved the mechanical threshold response in rats. In dorsal root ganglion, blocking hepatoma-derived growth factor inhibited inflammatory cytokines. In the spinal cord dorsal horn, blocking hepatoma-derived growth factor inhibited proliferation of astrocyte, apoptosis of neuron cells, and attenuated expressions of pain-associated proteins. The experiment showed that blocking hepatoma-derived growth factor can prevent neuropathic pain and may be a useful alternative to conventional analgesics.